2018
DOI: 10.33607/bjshs.v3i94.129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intervention “Hopsport Brain Breaks” Program on Physical Fitness and Sedentary Behaviour in Primary School

Abstract: Background. Sedentary behaviour in children raise concern as the majority of children do not meet the health-related level of physical activity (PA) which is closely related with their physical fitness (PF). Digital facilities may help to solve the problem. Hypothesis. After the intervention “HOPSport Brain Breaks” physical fitness improves and sedentary behaviour decreases. The aim of the study was to assess the effects of “HOPSport Brain Breaks” video exercise intervention program on physical fitness and sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 19 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…This idea is supported by Warburton et al (2007), who stated that such videos de-emphasize competitive fitness and foster an environment in which obese, overweight, and inactive children can easily participate. Tumynaitė et al (2014) determined that BB PA videos only affected the development of arm muscle strength and agility, but did not increase endurance, speed, and leg strength. Their study also determined that BB PA videos had a significant effect on reducing students’ sedentary behavior.…”
Section: Discussionmentioning
confidence: 94%
“…This idea is supported by Warburton et al (2007), who stated that such videos de-emphasize competitive fitness and foster an environment in which obese, overweight, and inactive children can easily participate. Tumynaitė et al (2014) determined that BB PA videos only affected the development of arm muscle strength and agility, but did not increase endurance, speed, and leg strength. Their study also determined that BB PA videos had a significant effect on reducing students’ sedentary behavior.…”
Section: Discussionmentioning
confidence: 94%
“…The researchers and the teachers worked closely to select from the list of various two- to five-minute videos, which included arts (dance and music); fitness skills (cardio and functional fitness); sports (skillastics, cycling, rowing); education (health issues, nutrition, and hygiene); and classroom activities (fun fitness, dynamic physical education) [ 18 ]. Each video contains a real or animated instructor to demonstrate the different exercises that would improve children’s motor and physical skills [ 11 , 45 , 46 ]. The teacher was trained regarding the choice of videos and presentation of the program.…”
Section: Methodsmentioning
confidence: 99%
“…Research has indicated a positive relationship between physical inactivity and obesity in this sense, negatively impacting children’s physical skills [ 10 , 11 , 12 ]. In accordance, De Milander [ 13 ] studied the relationship between PA, motor proficiency, and physical fitness in 12- to 13-year-old children and reported that lower motor and physical fitness skills result from declining PA levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations